Xenotransplantation of human unrestricted somatic stem cells in a pig model of acute myocardial infarction. (13th March 2013) - Gahremanpour, Amir; Vela, Deborah; Zheng, Yi; Silva, Guilherme V.; Fodor, William; Cardoso, Cristiano O.; Baimbridge, Fred; Fernandes, Marlos R.; Buja, L. Maximilian; Perin, Emerson C.
Abstract Background Stem cell therapy may help restore cardiac function after acute myocardial infarction (AMI), but the optimal therapeutic cell type has not been identified. Methods We examined the effects of CD34‐/CD45‐ human unrestricted somatic stem cells (USSCs) in pigs (n = 30) with an AMI created by a 90‐min occlusion of the left anterior descending coronary artery. Pigs were randomly assigned to receive either USSCs (302 ± 23 × 106 cells) or phosphate‐buffered saline via 15 NOGA‐guided transendocardial injections 10 days after AMI. Cyclosporine A (10 mg/kg orally, twice a day) was started in all pigs 3 days before control or cell treatment. Cardiac function was assessed by echocardiography before injection and at 4 and 8 weeks after treatment. Serum titers for pig IgG antibodies against USSCs were also measured at these time points and before AMI. Results Compared with control pigs, USSC‐treated pigs showed no significant differences in any of the functional parameters examined. USSC‐treated pigs showed variable increases in anti‐USSC IgG antibody titers in the blood and chronic inflammatory infiltrates at the cell injection sites. Immunohistochemical studies of the injection sites using human anti‐mitochondrial antibodies failed to detect implanted USSCs. Conclusions We conclude that human USSCs did not improve cardiac function in a pig model of AMI. Cell transplantation in a xenogeneic setting may obscure the benefits of stem cell therapy.